Apical sodium-dependent bile acid transporter inhibition with volixibat improves metabolic aspects and components of non-alcoholic steatohepatitis in Ldlr-/-.Leiden mice - Salic, Kanita (PLoS One, 2019)
Interruption of bile acid recirculation through inhibition of the apical sodium-dependent bile acid transporter (ASBT) is a promising strategy to alleviate hepatic cholesterol accumulation in non-alcoholic steatohepatitis (NASH), and improve the metabolic aspects of the disease. Potential disease-attenuating effects of the ASBT inhibitor volixibat (5, 15, and 30 mg/kg) were investigated in high-fat diet (HFD)-fed Ldlr-/-.Leiden mice over 24 weeks. Plasma and fecal bile acid levels, plasma insulin, lipids, and liver enzymes were monitored. Final analyses included liver histology, intrahepatic lipids, mesenteric white adipose tissue mass, and liver gene profiling. Consistent with its mechanism of action, volixibat significantly increased the total amount of bile acid in feces. At the highest dose, volixibat significantly attenuated the HFD-induced increase in hepatocyte hypertrophy, hepatic triglyceride and cholesteryl ester levels, and mesenteric white adipose tissue deposition. Non-alcoholic fatty liver disease activity score (NAS) was significantly lower in volixibat-treated mice than in the HFD controls. Gene profiling showed that volixibat reversed the inhibitory effect of the HFD on metabolic master regulators, including peroxisome proliferator-activated receptor-γ coactivator-1β, insulin receptor, and sterol regulatory element-binding transcription factor 2. Volixibat may have beneficial effects on physiological and metabolic aspects of NASH pathophysiology.